Nutrition needs for team sport - Williams, C.; Nicholas, C. W. (1998)
High-carbohydrate, pre-exercise meals improve exercise capacity. Carbohydrate-electrolyte drinks ingested during exercise are of benefit during competition and training. Fluid ingestion during prolonged exercise helps delay the deterioration in motor skills. Recovery is improved when about 50 g of carbohydrate are consumed immediately after prolonged exercise and at 1-h intervals thereafter. During daily training or competition, recovery is likely to be improved when carbohydrate intake is increased to 10 g per kg body weight each day. Rehydration is quickly achieved during recovery when athletes ingest fluids equivalent to at least 150% of the body weight lost during the exercise.